Collaborative logistics: a study among small and medium sized supermarkets and their suppliers - Vieira, José Geraldo Vidal; Machado, Vitor Rocha (Revista Gestão da Produção Operações e Sistemas, 2008)
In recent years, the supermarket sector has undergone several changes, especially related to the relationship among its members, when searching for collaborative logistics. This research characterized the logistics structure of small-size supermarkets in Minas Gerais, Brazil, and it evaluated the level of collaboration and the logistics performance of its suppliers by means of exploratory and descriptive techniques and uni and multivariate analysis. One may conclude that logistics collaboration is still found in an initial stage and furthermore, the logistics performance is considered to be satisfactory by the retailers Keywords: Collaborative logistics, Logistics performance, Retail business.